2009
DOI: 10.1007/s10103-008-0639-y
|View full text |Cite|
|
Sign up to set email alerts
|

Heat conduction from the exceedingly hot fiber tip contributes to the endovenous laser ablation of varicose veins

Abstract: Lower-extremity venous insufficiency is a common condition, associated with considerable health care costs. Endovenous laser ablation is increasingly used as therapy, but its mechanism of action is insufficiently understood. Here, direct absorption of the laser light, collapsing steam bubbles and direct fiber-wall contact have all been mentioned as contributing mechanisms. Because fiber tips have reported temperatures of 800-1,300°C during endovenous laser ablation, we sought to assess whether heat conduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Only administration of a relatively high energy per unit of length results in sufficiently high temperatures to cause denaturing of collagen. 33 During endovenous laser ablation, intraluminal temperatures can rise to over 100ºC, 28,[34][35][36][37][38][39] and these temperature profiles are independent of wavelength, i.e. use of different wavelengths does not influence the endovenous temperature profile.…”
Section: Adverse Events N (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only administration of a relatively high energy per unit of length results in sufficiently high temperatures to cause denaturing of collagen. 33 During endovenous laser ablation, intraluminal temperatures can rise to over 100ºC, 28,[34][35][36][37][38][39] and these temperature profiles are independent of wavelength, i.e. use of different wavelengths does not influence the endovenous temperature profile.…”
Section: Adverse Events N (%)mentioning
confidence: 99%
“…33 Since the coefficient of molar extinction is similar for water and blood, when a laser with a wavelength of 1470nm or 1940nm is used, it is important to empty the vein of intraluminal blood, 33 because otherwise the majority of the energy will be absorbed by the intraluminal blood, leading to thrombotic occlusion and possible recanalization after a few months. 27,33,37,38 This statement is based on a study by Vuylsteke et al, 33,40 that assessed the role played by blood in the results of endovenous treatment with a 1500nm laser, histologically evaluating the degree of destruction of the vein wall. The study concluded that the volume of intraluminal blood results in a reduction of vein wall destruction.…”
Section: Adverse Events N (%)mentioning
confidence: 99%
“…The formation of these steam bubbles has been confirmed by Proebstle et al [9] who have observed that they were generated in hemolytic blood by 810, 940, and 980 nm diode lasers, whereas no bubbles were produced in normal saline or plasma However, this mechanism is now considered of secondary importance for EVLA efficacy [1].…”
mentioning
confidence: 61%
“…Several experimental studies were recently published in order to give a better understanding on the mechanism of action of endovenous laser ablation (EVLA) [1][2][3][4]. The experimental model is usually a human vein segment filled with heparinised blood [1,2].…”
mentioning
confidence: 99%
See 1 more Smart Citation